TRANSFORMASI AGENDA PEMBANGUNAN GLOBAL (MDGs-SDGs) DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN - Resti S (WANUA : Jurnal Hubungan Internasional, 2017)
Nowadays, the problems as such famine, gender inequality, lack of water resources, and many other problems are no longer belong to individual and any specific countries. These problems have become a global problem in this era of globalization. This global problem then raises the global response by forming a global development agenda in the form of MDGs which then continued by SDGs with more complex goals. The addition of goals and strategic change from MDGs to SDGs is also a form of response to increasingly complex global issues and requires serious handling. The participation of the state and the international community is needed for the achievement of the goals to be achieved. Many are optimistic about the transformation but not the least are pessimistic on the transformation of this global development agenda. Optimists argue that SDGs are more promising because they promote principles that uphold justice and equality. While pessimists argue that the process of preparing SDGs is not purely based on global issues but is heavily influenced by political processes, such as Chinese politics which ensures that no word of democracy emerges in the goals of SDGs. It is important to discuss whether the transformation is something that can make a significant difference. To analyze this question, a sustainable development perspective can be used. The transformation is seen as a manifestation of development that moves forward along with the fear (traumatism) of other problems that will arise with global problems, such as chaos, conflict to war. This then makes economic restructuring and global development scheduled along with the process of achieving peace.